Cunninghamella saisamornae (Cunninghamellaceae, Mucorales), a new soil fungus from northern Thailand - Suwannarach, Nakarin; Kumla, Jaturong; Supo, Chantana; Honda, Yoichi; Nakazawa, Takehito; Khanongnuch, Chartchai; Wongputtisin, Pairote (Phytotaxa, 2021)
A new endophytic fungus, described herein as Cunninghamella saisamornae, was isolated from soil collected from Chiang Mai Province, Thailand. This species was distinguished from the previously described Cunninghamella species by the presence of a chlamydospore formation, the lack of a zygospore stage and a maximum growth temperature of 45°C. Multi-gene phylogenetic analysis of internal transcribed spacers (ITS) and large subunit (LSU) of the nuclear ribosomal DNA (rDNA), along with the translation elongation factor 1-alpha (tef-1) genes, support the finding that C. saisamornae is distinct from other species within the genus Cunninghamella. A full description, color photographs, illustrations and a phylogenetic tree showing the position of C. saisamornae are provided.